COLONY FOUNDING AND LIFE-CYCLE IN THE ANT CAMPONOTUS SERICEUS FABRICIUS (HYMENOPTERA: FORMICIDAE) - BASALINGAPPA, S.; KAREDDY, VISHWANATH B.; MATHAPATHI, S. B.; GANDHI, MEENA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1989)
After the nuptial flight, in the months of September and October only dealate females were observed, searching for suitable nesting sites and to excavate their nests. Alate males did not participate in such activities. Each dealate female made a vertical burrow and the broodchamber was formed at the blind end of the nest. In 80% of the cases a single female was involved in colony founding under laboratory conditions, but only in 20% of the cases more than one individuals were involved. Duration of the life-cycle under natural conditions in the field and under laboratory conditions, with near natural conditions was more or less similar i. e. 24 to 26 and 21 to 30 days respectively. Whereas duration of the life-cycle under laboratory condition with and without media was 40 and 55 days respectively. Developmental period of different life stages of the ant C. sericeus was dependent on temperature and media.